Retrato do ensino não presencial em escolas públicas do município de Benjamin Constant – AM em tempos de pandemia de COVID-19 - Acris, Danielly (Brasil, 2022)
The disease caused by the new Covid-19 has affected several lives worldwide. In this way, some routine human actions such as work, study, and interaction with other people have undergone drastic changes, with the implementation of Biosecurity measures to contain the advance of the pandemic. Measures for sanitary control were recommended by governments and health authorities, directly affecting the country's education sector. Due to this challenge, the government, through the MEC, made in-person classes of all levels and spheres more flexible to continue their activities remotely. Based on these questions, it carried out a research with a qualitative-quantitative approach, of the descriptive and exploratory type, characterized by being a field research, and aimed to know the experience of remote teaching by teachers of the disciplines of Natural Sciences, Biology and Chemistry of the Basic education in times of Covid-19 Pandemic in Benjamin Constant - Am. In this way, the research contributed to broadening the debate on the experience of remote teaching by elementary school teachers in times of the Covid-19 Pandemic, as well as making it possible to identify the main difficulties encountered by teachers. In addition, there was a description of the procedures and methodological tools used by the teachers, verifying how the remote classes were contextualized.